Kazakhstan-China cooperation in frame of new Silk road economic belt (International relations and international law Journal, 2016)
China is the largest external trade partner of Kazakhstan. A new stage of the relations between Kazakhstan and China are elaborated with new projects in all bilateral cooperating spheres. The President of Kazakhstan N.Nazarbayev’sinitiative of the new economic policy «NurlyZhol» (Bright Path) and the President of the PRC Xi Jinping’s «One Belt, One Road» initiative within the framework of «theSilk Road Economic Belt» and «the 21st-century Maritime Silk Road» strategic projectsare also ministerial to it. Transport and logistics intend to be the main component of the Silk Road Economic Belt. For Kazakhstan realization of the project is considerable diversification of its sources of profit and decrease exposure on world oil prices, as for China it gives an opportunity to land transportation of own production to Kazakhstan, Russia and Europe.
Keywords: the Republic of Kazakhstan; China; «NurlyZhol»; «Silk Road Economic Belt»; «One Belt; One Road»; cooperation